Role of catalyst supports in biocatalysis. Issue 1 (28th July 2022) - Manikandan, Soumya Koippully; Giannakoudakis, Dimitrios A.; Prekodravac, Jovana R; Nair, Vaishakh; Colmenares, Juan Carlos
Abstract: Biocatalysis utilizes enzymes and microbial cells as catalysts for a wide range of applications in biotechnology. Immobilization of biocatalysts on various materials has several advantages, including the capacity for reuse, quick reaction termination, easy biocatalyst recovery and operational stability. The present article focuses on the use of material supports for developing immobilized biocatalysts in applications related to energy, environment and chemical synthesis. The work provides a comprehensive overview of a broad class of materials, including organic, inorganic and composites, that have been shown to be prosperous candidates to support the immobilization of enzymes and microbial cells. It also highlights the properties of nanomaterial support such as large surface area and comfort compartment for immobilization. The availability of different types of materials as catalyst support provides an opportunity to understand and develop efficient biocatalytic systems. The choice of selecting a catalyst support will mostly depend on the interaction of the material with the enzyme or microbial cell. Finally, potential challenges, future approaches in developing immobilized biocatalytic systems for various applications and novel material supports are suggested. © 2022 Society of Chemical Industry (SCI).